Pengaruh Disiplin Kerja Dan Motivasi Terhdap Kinerja Pegawai Di SMK IT Annaba Bogor - Rosmiati, Reni; Agung , Syahrum; Huriyaturrohman, Huriyaturrohman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the effect of work discipline and motivation on the performance of SMK IT ANNAB Bogor Vocational High School Employees. This type of research is quantitative. The population of this study were employees of SMK IT ANNAB Bogor using a saturated sampling technique with a total population of 40 respondents. The research instrument is a questionnaire. The results of the research instrument test used multiple regression analysis tests, t tests, and f tests. The results of this study were that the Work Discipline Variable (X1) has a positive relationship to the Employee Performance variable (Y), which means that if there is an increase in Work Discipline, the Employee Performance will also will increase. The motivation variable (X2) has a positive relationship to the employee performance variable (Y), which means that if there is an increase in motivation, employee performance will also increase. Work Discipline variable (X1) and Motivation variable (X2) have a positive relationship to Employee Performance variable (Y), which means that if there is an increase in the independent variable, the dependent variable will also increase